ALISHER NAVOIY “MAJOLIS UN-NAFOIS” AND ITS HISTORICAL SIGNIFICANCE (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article examines Alisher Navoiy’s work *Majolis un-nafois* from historical-literary, theoretical, and source-study perspectives. It discusses the conditions of its creation, structure, genre features, its contribution to the development of literary criticism, and the role of the work in reflecting the cultural environment of the 15th century. The research results indicate that “Majolis un-nafois” is an important scholarly and literary source that established an independent school of Turkic (Chagatai) tazkirah.
Keywords: tazkirah, Chagatai literature, literary criticism, biographical genre, source studies, aesthetic criteria.